Representation of Aesthetic Value in Bugis and Makassar Classic Song - Ulinsa Ulinsa; Abdul Gafur Marzuki; Agung Surya Laksana; Nursyamsi Nursyamsi; M. Asri B (Universitas Cokroaminoto Palopo, 2023)
The purpose of this research is to describe or know and explain the aesthetic value contained in classical Bugis and Makassar songs. This research is qualitative. The data sources of this research are Bugis songs and classical Makassar songs. The research instrument consisted of a gadget or mobile phone, a youtube application, and writing instruments in the form of books and pens. The research method used is a type of qualitative research, which is a research procedure that uses data or descriptive methods in the form of written or spoken words that can be observed. Data were collected using interviews, observation, and documentation studies, where documents in the form of audio and audio-visual will be transcribed into a written form which will then be analyzed for the aesthetic meaning contained therein. The result showed that classical Bugis and Makassar songs have aesthetic values in the form of 1) the value of sacrifice, 2) the value of love/affection, 3) the value of morals/life, and 4) the value of culture. The value of sacrifice contained in Bugis and Makassar songs is a sacrifice made or given to people who are loved sincerely, then for the value of love/affection contained in Bugis and Makassar songs in the form of stories about problems of love or the beauty of that love itself, then for the moral/life values contained in the Bugis and Makassar songs, it gives a message about good behavior or ethics in living life, and for cultural values, it provides lessons about the importance of working together and maintaining tolerance among others.